The kappa-opioid receptor agonist, nalfurafine, blocks acquisition of oxycodone self-administration and oxycodone's conditioned rewarding effects in male rats. Issue 8 (December 2020) - Zamarripa, C. Austin; Patel, Tilak R.; Williams, B. Cole; Pareek, Tanya; Schrock, Hayley M.; Prisinzano, Thomas E.; Freeman, Kevin B.
Abstract : Mu-opioid receptor (MOR) agonists are highly efficacious for the treatment of pain but have significant abuse liability. Recently, we reported that nalfurafine, when combined with oxycodone at a certain ratio, reduced the reinforcing effects of oxycodone in rats while producing additive antinociceptive effects. Questions remain, however, including if the combination will function as a reinforcer in drug-naïve rats, and if the combination produces aversive effects that could explain nalfurafine's ability to reduce oxycodone self-administration? In the present study, we investigated nalfurafine's ability to reduce acquisition of oxycodone self-administration when the two were self-administered as a mixture in drug-naïve rats and nalfurafine's ability to attenuate a conditioned place preference (CPP) induced by oxycodone. In the self-administration study, male Sprague–Dawley rats self-administered intravenous injections of oxycodone (0.056 mg/kg/injection), an oxycodone/nalfurafine combination (0.056/0.0032 mg/kg/injection), or saline under fixed-ratio schedules of reinforcement for 20 days to compare rates of acquisition of drug taking. In the CPP assay, male Sprague–Dawley rats received subcutaneous injections of either saline, oxycodone (3.2 mg/kg), nalfurafine (0.18 mg/kg), or an oxycodone/nalfurafine combination at the same ratio used in the self-administration study (3.2 mg/kg/0.18 mg/kg). All subjects self-administering oxycodone alone met acquisition criteria. However, only 13% of subjects self-administering oxycodone/nalfurafine met criteria, and no subjects acquired self-administration of saline. Oxycodone, but not nalfurafine alone or the oxycodone/nalfurafine combination, produced rewarding effects in rats in the CPP test. These findings suggest that the combination of oxycodone and nalfurafine will be less habit forming in opioid-naïve patients than oxycodone alone.